Considerations for a European animal welfare standard to evaluate adverse phenotypes in teleost fish - Bert, Bettina; Chmielewska, Justyna; Bergmann, Sven; Busch, Maximilian; Driever, Wolfgang; Finger-Baier, Karin; Hößler, Johanna; Köhler, Almut; Leich, Nora; Misgeld, Thomas; Nöldner, Torsten; Reiher, Annegret Lucia; et al. (The EMBO journal, 2016)
The EU Directive on the use animals in research requires scientists to assess and document pain, distress or lasting harm of genetically modified animals. This article proposes a detailed protocol and guidelines for assessing adverse phenotypes in teleost fish, an important model organism for biomedical research.
Gesehen am 07.05.2020